Élites intellectuelles françaises, élites intellectuelles grecques et la « question de la langue » en Grèce dans les années 1920 et 1930 : le cas de Louis Roussel - Julien Calvié (Cahiers Balkaniques)
Louis Roussel was a pioneer in the history of neo-hellenism in France. His journal, Libre, which was published regularly from December 1922 until July 1936, offered a deep and vivid insight into the intellectual life in Athens during the twenties and thirties.Using Libre, we shall study successively the representation of the partisans of katharevousa and the representation of the demoticists. We shall conclude by establishing that, concerning the “language question” in Greece, Louis Roussel’s viewpoint was both philhellenic and republican: no elite reserved language, the same language must be used by everyone, and it is therefore this one and the same language that is to be used in everyday life, in school, in the newspapers, in literature and in sciences. In this way, everyone will have an equal access to knowledge and Greece may become a nation.